PENGARUH CORPORATE SOCIAL RESPONSIBILITY DISCLOSURE DAN MANAJEMEN LABA TERHADAP LEGITIMASI INVESTOR - Bahrul Amiq; Nor Hadi (AKSES: Jurnal Ekonomi dan Bisnis, 2015)
The purpose of research to analyze and prove the influence of whether corporate socialresponsibility disclosure and earnings management affect the legitimacy of investors. Theresearch was conducted at Go Public company listed on Indonesia Stock Exchange. The dataused are secondary data in the form of annual report / annual report of each company from2010-2012. Independent variables used are corporate social responsibility disclosure andearnings management, while the dependent variable used by investor legitimation. CSR usesCorporate Social Disclosure Index (CSDI) indicators, while earnings management uses totalaccruals. Data analysis method used to test the hypothesis is multiple linear regression. Theresult of SPSS analysis shows the first hypothesis is rejected by t-count 1,223 andsignificance value 0,230. The second hypothesis is accepted by t-count -3,362 and thesignificance value is 0.002. The third hypothesis is received with f-count of 5.781 and thesignificance value is 0.007. The coefficient of determination is 0.272 or 27.2%.Keywords: Corporate Social Responsibility Disclosure, Profit Management and InvestorLegitimacy